Drug survival and predictor factors for discontinuation of methotrexate in psoriasis: A real-life multicenter study - Özkök Akbulut, Tuğba; Topaloğlu Demir, Filiz; Topal, İlteriş Oğuz; Kara Polat, Asude; Karadağ, Ayşe Serap; Aslan Kayıran, Melek; Özkur, Ezgi; Kıvanç Altunay, İlknur (Wiley, 2021)
Background Drug survival is useful to evaluate long-term drug performance in daily practice. The aim of this study was to evaluate drug survival for methotrexate (MTX) monotherapy in patients with plaque-type psoriasis. Methods We reviewed 3,512 follow-up charts of patients with psoriasis at five tertiary referral centers between January 2012 and January 2020. We analyzed baseline data and treatment outcomes of patients under MTX monotherapy. Drug survival was analyzed using Kaplan-Meier and Cox regression analyses. Results Patients with psoriasis who were treated with MTX monotherapy were enrolled (N = 649). The median duration of drug survival was 15 months (95% CI: 13.2-16.8). The overall drug survival rate was 54.7%, 17.4%, and 8% after 1, 3, and 5 years, respectively. The main reasons for discontinuation were adverse effects (n = 209, 32.2%) and inefficacy (n = 105, 15.6%). Based on multivariate Cox regression analysis, the presence of nausea/vomiting (HR: 2.01, 95% CI: 1.49-2.71; P < 0.001) was observed as a statistically significant risk factor for drug discontinuation. Age over 50 years (HR: 0.68, 95% CI: 0.48-0.97; P = 0.03) and using MTX dose >= 15 mg/weekly were positive predictors for drug survival (HR: 0.72, 95% CI: 0.54-0.95; P = 0.02). Conclusions The average drug survival of MTX was 15 months. MTX is still the first-line treatment of moderate-to-severe plaque psoriasis, as highlighted in guidelines. To prevent premature discontinuation, physicians need to look at the response time of at least 16-24 weeks, especially when a stepwise dose increment is used. The presence of nausea/vomiting seemed to be associated with an approximately twofold risk of discontinuation.
Keywords: Predictor Factors; Drug Survival; Methotrexate